Power plays politics, football, and other blood sports - Barry, John M. (Univ. Press of Mississippi, 2001)
Barry, a former Washington journalist and college football coach, compares the abuse of power in politics and sports.
Keywords: USA -- Government; Geschichte 1900-2000; Geschichte 1989-2000; Geschichte; Gesellschaft; Politik; Athletes -- United States -- Biography; Football -- Social aspects -- United States -- History -- 20th century; Political corruption -- United States -- History -- 20th century; Politicians -- United States -- Biography; Power (Social sciences) -- United States -- History -- 20th century; Sports -- Social aspects -- United States -- History -- 20th century; Macht; Soziale Rolle; Sport; Machtpolitik; USA; United States -- Politics and government -- 1989-; Biografie